Diagnostic accuracy of screening tests for eating disorders in adolescents and adults in primary health care: protocol for systematic review and meta-analysis - Thiala Santos Duarte de Oliveira; Mônica Leila Portela de Santana; Valterlinda Alves de Oliveira Queiroz; Karine Brito Beck da Silva; Poliana Cardoso Martins; Emile Miranda Pereira; Priscila Ribas de Farias Costa (BMJ Open)
Introduction Eating disorders can be irreversible and, in many cases, fatal. However, the symptoms full recovery is possible, and early diagnosis is one, of many, important factors for the success of treatment. In this sense, the screening of risk behaviours arises as a relevant alternative to improve the prognosis of patients. This review will analyse the diagnostic accuracy of self-administered screening tests for eating disorders in adolescent and adult users of primary healthcare.Methods and analysis A systematic review will be performed by independent reviewers. The databases used will be Medline, Embase, the Latin American and Caribbean Health Sciences Literature, the Cumulative Index to Nursing and Allied Health Literature, Web of Science, PsycINFO, ProQuest Dissertations and Theses Database and Google Scholar without restrictions on the year of publication and language. Studies that compared the results of self-administered screening tests for eating disorders in adolescents and adults in primary care with the results of clinical interviews will be included. Data extraction will consist of the identification of the publication, study and participant characteristics, general information about the tools and data on the diagnostic accuracy properties. The risk of bias in the studies will be assessed via the Quality Assessment of Diagnostic Accuracy Studies. Qualitative data will be presented in narrative form. The meta-analysis will be conducted via the random effects model with the metadata command of Stata. The summary statistics for sensitivity and specificity, as well as their 95% CI, will be generated.Ethics and dissemination This systematic review is based on published literature; therefore, submission to an ethics committee is not necessary. The dissemination of the study will be carried out through technical reports, scientific articles, posters, meeting presentations, specific forums, national congresses and international media.PROSPERO registration number CRD42023476156.